Low-Lying Rectal Cancer With Anal Canal Involvement: Abdominoperineal or Low Anterior Resection After Neoadjuvant Chemoradiotherapy - Do, Ly (International Society of Gastrointestinal Oncology, 2011)
BACKGROUND: Rectal cancer with anal involvement is typically treated with abdominoperineal resection (APR). However, patients treated with neoadjuvant chemoradiotherapy with good clinical response and tumor regression from the anus present a controversial management dilemma. This is a report of patients treated with low anterior resection (LAR) versus APR. METHODS: Patients with T2–3N0–2M0 (IIA-IIIC) rectal cancer with anal canal involvement were eligible. Anal canal involvement was determined by sigmoidoscopy/colonoscopy or endoscopic ultrasound. Patients were treated in the prone position with the three-field technique to 45–50.4 Gy at 1.8 Gy/fraction given concurrently with 5-fluorouracil. Patients then underwent APR/LAR via total mesorectal excision 4–6 weeks after chemoradiotherapy. LAR was performed in patients with good sphincter function at presentation, in those with sufficient tumor regression away from anal canal to permit LAR, and in those compliant with close follow-up. RESULTS: A total of 32 patients with rectal cancer with anal canal involvement were treated with neoadjuvant chemoradiotherapy. Local control was 85% and 89% for patients treated with APR and LAR, respectively. Overall survival was 76% and 86% in patients treated with APR and LAR, respectively. Pathologic complete response was seen in 24% of patients who underwent APR and 27% of patients who underwent LAR. CONCLUSION: Rectal cancers with anal involvement with good clinical response after neoadjuvant chemoradiotherapy are typically treated with APR. However, LAR may be a feasible alternative, particularly in those with excellent clinical response to neoadjuvant treatment with sufficient tumor regression away from the anal canal. In these patients close follow-up is necessary, and APR may be reserved as salvage when needed.